Pengaruh Kompensasi Dan Motivasi Terhadap Kinerja Karyawan Pada PT. Jaya Teknik Artha Makmur Tangerang - Lely Balqis Hasanah; Irwin Ananta Vidada; Seno Sudarmono Hadi (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
Human resources are the driving aspect of a company's operations. The performance of human resources, namely employees, is an essential factor in achieving company goals. Providing proper compensation and motivation will influence employee performance. This study aims to determine the effect of compensation and motivation on employee performance at PT. Jaya Teknik Artha Makmur Tangerang. A non-probability technique of 41 employees chose the sample, and the analytical method used was multiple linear regression analysis. The result of this study indicates that partial compensation does not significantly influence employee performance, but the coefficient value is positive. This result showed the value of t count -0,102 < t table 1,685 with a significant level > 0,919. In comparison, motivation significantly affects employee performance with a positive coefficient value. The t count also indicates the t count 5,349 > t table 1,685 with a significant level < 0,000. Simultaneously compensation and motivation affect performance.